2012
DOI: 10.1177/1049909111435811
|View full text |Cite
|
Sign up to set email alerts
|

Most Advance Directives Written by Patients With Advanced Cancer or Their Proxies Request Only Minimally Invasive Treatments During End-of-Life Care

Abstract: Although it is assumed that most patients with terminal cancer are reluctant to receive life-sustaining treatment, there is a paucity of evidence supporting this assumption. We retrospectively analyzed the advance directives of terminal cancer patients to determine the preferences of patients. Patients with cancer who had life expectancy of less than 6 months were admitted to a palliative care unit in Seoul Medical Center from March 2008 to February 2010. Among a total of 247 patients, advance directives were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 9 publications
0
15
1
Order By: Relevance
“…Many studies have emphasized the importance of advance directives, which often are not collected or transmitted but may be of major importance in the case of a patient with cancer and delirium presenting to the ED . However, this is in contrast to the results of a study performed in patients with advanced cancer, which found that advance directives were present in 68.0% of the medical records, with the majority of them written by the patients' families (95.2%) and stating that they did not want most of the invasive procedures …”
contrasting
confidence: 89%
“…Many studies have emphasized the importance of advance directives, which often are not collected or transmitted but may be of major importance in the case of a patient with cancer and delirium presenting to the ED . However, this is in contrast to the results of a study performed in patients with advanced cancer, which found that advance directives were present in 68.0% of the medical records, with the majority of them written by the patients' families (95.2%) and stating that they did not want most of the invasive procedures …”
contrasting
confidence: 89%
“…Although this value is lower comparing with the existing research, it is meaningful that all ADs were completed by patients themselves. Kwon et al ( 4 ) reported that 68% of patients in hospice centers had ADs completed, but only 4.8% were conducted by patients. The purpose of ADs is to reflect patients' self-determination and protect their autonomy.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, it took the patients a median of three days to complete ADs, and they died 22 days after signing ADs. Kwon et al ( 4 ) reported that the median duration of survival after ADs were signed was nine days. In our study, ADs were completed relatively earlier; however, the duration of survival after the patients signed ADs is still very short.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Choi et al [24] reported that the rate of discontinuing life-prolonging treatment according to the patient's intent (69.0%) was higher than that according to the family or agent (50.5%). In the research of Kwon et al [25], in contrast, the form was prepared mostly by families (95.2%). Hence, with regard to who should make the form of AD and make decisions about meaningless life-prolonging treatment, opinions need to be gathered sufficiently from the medical circles, academic circles, civil organizations, public, patients, and guardians.…”
Section: Investigation and Conclusionmentioning
confidence: 99%